A67 EVALUATING ACCESS TO IBD CARE ACROSS CANADA: PROCEEDINGS FROM THE 2017 IBD ACCESS SUBMMIT. (26th February 2020) - MacDonald, S; Heisler, C; Mathias, H; Mirza, R; Jones, J
Abstract: Background: Inflammatory Bowel Disease (IBD) is a chronic, immune-mediated disease, with Canada demonstrating the highest incidence and prevalence rates in the world. Patients with IBD often require lifelong treatment and, therefore, lifelong interactions with the healthcare system. Access to care can have a direct impact on patient health-related outcomes. Although acknowledged as a problem, the complexity of accessing IBD specialty care in Canada has not been reviewed. This lack of understanding presents a barrier in evaluating and implementing changes in IBD specialty care. Aims: To identify key barriers and facilitators for and to develop a national working strategy to address limitations in access to IBD specialty care by exploring the perceptions and experiences of key stakeholders (pediatric and adult gastroenterologists, IBD patients, researchers, and policy makers). Methods: The IBD Summit was held in Toronto, Ontario in November 2017, sponsored by SPOR-CIHR catalyst funding and in partnership with Crohn's & Colitis Canada. Perceptions and experiences of key stakeholders were gathered during two audio-recorded stakeholder dialogues held during the Summit. The audio recordings were transcribed and coded to compare and contrast between key stakeholders to determine potential differences in access to IBD care. Five final themes are highlighted in this report. Results: A total of 21 key stakeholders attended, including pediatric and adult gastroenterologists, patients, researchers, and policy makers. Five key themes of importance relating to access to IBD care arose from The IBD Summit:(1) Integrated Models of Care, (2) IT Enhanced Care, (3) Health System Process, (4) Communication and Advocacy, and (5) Community Supports. The IBD Summit identified similar perceptions and experiences, highlighting common barriers and facilitators that transcend provincial borders. Shared perceptions included a need for common medical records and overall improved IT-enhanced care for managing IBD; improved centralized triage systems; increased comprehensive care support for patients and primary care physicians; and increased community supports for patients and providers. Conclusions: Highlights from the IBD Summit present several clinically relevant and actionable suggestions for improved access to IBD speciality care across Canada. The suggestions provided by key stakeholders highlight the need for a system-level redesign in order to improve access to enhanced models of care. Improvements in access to IBD specialty care can only occur through partnerships between those working within the healthcare system and those within the community. Future research will involve pursuing deeper insight into the experience of patient and provider stakeholders as they navigate the healthcare system in order to access and provide care. Funding Agencies: CIHRNova Scotia Health Authority Research Fund